PENGARUH KEPERCAYAAN PADA PERUSAHAAN TERHADAP BEHAVIORAL LOYALTY MELALUI KOMITMEN PEMASARAN RELASIONAL KLIEN JASA TRANSPORTASI BARANG PT. PELNI CABANG SURABAYA - Ira Ningrum Resmawa (Politeknik Negeri Sriwijaya, 2015)
The focus of this research is to analize the influence of trust upon behavioral loyalty with relational commitment as mediating variable. In this research, we trust were measured by reliability and integrity of PT. PELNI. Relational commitment were measured by resistance to change. On the other hand, behavioral loyalty were measured by brand preference and repeat purchase. Samples of the research are 25 companies that use PT. PELNI services in Surabaya. Data obtained from the research are analyzed by applying the SPSS program of 13.0. The SPSS program was used for executing staristical technique analysis, namely Linear Regression. The result of the research indicated that (1) trust significantly influence relational commitment (hypothesis is accepted); (2) relational commitment significantly influence behavioral loyalt (hypothesis is accepted).